Tanggung Jawab Pemerintah Daerah Kabupaten Maluku Barat Daya Dalam Pengelolaan Wisata Pantai - Kostafina Silety (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
Authority to the Regency Regional Government in managing Beach Tourism to provide benefits for people's welfare, equality, proportionality, justice, maintaining natural and environmental sustainability, empowering local communities. This research is a normative juridical research on this problem and then examines and knows the answers to this problem through a conceptual approach, statutory approach then from the results of the description conclusions and suggestions can be drawn. The results of the study show that the Regional Government of Southwest Maluku Regency has the responsibility for managing beach tourism in the area in accordance with Law Number 10 of 2009 concerning Tourism as the scope of authority in tourism matters. On the other hand Law Number 23 of 2014 concerning Regional Government gives authority to manage sea areas only to the Regional Government in this case the Regional Government of the Maluku Province and is not given to the Regional Government of the Regency/City in this case the Regional Government of Southwest Maluku Regency and the Forms of Responsibility The Regional Government of Southwest Maluku Regency in managing beach tourism is implementing the authority granted by Law Number 10 of 2009 concerning Tourism which in principle prepares tourist attractions/attractions, tourist infrastructure and forms micro business groups by providing grants and asking the Government The Maluku Province Region to provide concurrent affairs for the management of the sea area to the Regional Government of Southwest Maluku Regency so that it can develop tourism potential in the sea area.